A METHODOLOGY FOR THE READING OF YELLOW TRAPS USED IN THE EVALUATION OF WHITE FLY IN A COMMERCIAL TOMATO CULTIVATION - ESPAÑOL, JEANNETTE A.; CORREDOR, DARÍO (Revista Colombiana de Entomología, 1989)
Population dynamics of the greenhouse whitefly Trialeurodes vaporariorum (Westwood) was studied in a tomato crop by using sticky yellow traps. The plastic pipe used as a trap was 0.1 m in diameter and 1.5 m high. The number of adult whiteflies was counted by square centimeter and the traps were divided in higher, medium, and lower vertical sections of 0.45 m each. These sections were subdivided into nine horizontal strips of 0.05 m wide each. A good estimate of the population was obtained by counting the whiteflies on four of the nine horizontal stripes for a vertical section. According to the age of the tomato crop, the lower vertical section of the trap has to be sampled from day 1 to 30, the medium section from day 31 to 50, and the higher section of the trap from day 51 to 112.